2017
DOI: 10.1016/j.bbr.2017.07.022
|View full text |Cite
|
Sign up to set email alerts
|

Pre- and post-natal melatonin administration partially regulates brain oxidative stress but does not improve cognitive or histological alterations in the Ts65Dn mouse model of Down syndrome

Abstract: Melatonin administered during adulthood induces beneficial effects on cognition and neuroprotection in the Ts65Dn (TS) mouse model of Down syndrome. Here, we investigated the effects of pre- and post-natal melatonin treatment on behavioral and cognitive abnormalities and on several neuromorphological alterations (hypocellularity, neurogenesis impairment and increased oxidative stress) that appear during the early developmental stages in TS mice. Pregnant TS females were orally treated with melatonin or vehicle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 90 publications
1
15
0
Order By: Relevance
“…Similarly, despite melatonin-exerted neuroprotection and induced pro-cognitive effects observed when it was administered during adult stages to Ts65Dn mice, its administration during pre-and postnatal stages did not prevent or reduce the cognitive impairment of these animals. The differences found between the administration of this indoleamine to Ts65Dn mice during early and late stages were probably due to the different doses used in each case, or to the well-known differences in pharmacokinetics between infancy and adulthood [80].…”
Section: Antioxidant Therapies In Early Life Stagesmentioning
confidence: 97%
See 1 more Smart Citation
“…Similarly, despite melatonin-exerted neuroprotection and induced pro-cognitive effects observed when it was administered during adult stages to Ts65Dn mice, its administration during pre-and postnatal stages did not prevent or reduce the cognitive impairment of these animals. The differences found between the administration of this indoleamine to Ts65Dn mice during early and late stages were probably due to the different doses used in each case, or to the well-known differences in pharmacokinetics between infancy and adulthood [80].…”
Section: Antioxidant Therapies In Early Life Stagesmentioning
confidence: 97%
“…The Ts65Dn mouse, the best characterized and the most commonly used model of DS, shows increased OS (lipid peroxidation and protein carbonylation) and mitochondrial dysfunction in the hippocampus and cortex [77][78][79][80][81][82][83], that affects brain structure and function [75]. Although, to the best of our knowledge, oxidative DNA damage has not been studied in the brain of this model, it has been demonstrated that other cell types such as satellite cells of skeletal myofibers and hematopoietic stem cells accumulate oxidative DNA damage and prematurely develop a senescent phenotype in the Ts65Dn mouse [84][85][86].…”
Section: Brain Oxidative and Mitochondrial Profile In Mouse Models Of Dsmentioning
confidence: 99%
“…It was reported that melatonin rescued the neurogenesis suppression in the Ts65Dn (TS) mice by increasing the density and activity of glutamatergic synapses [ 112 ]. Nevertheless, in another study, it was shown that melatonin had no effect on the improvement of neurogenesis and behavioral outcomes in TS mice, but only regulated the DS-induced oxidative stress [ 113 ] ( Table 12 ).…”
Section: Melatonin and Other Diseases That Are Related To Neurogenmentioning
confidence: 99%
“…Levels of oxidative stress, i.e., high ratio between SOD1 and GPx, correlated with cognitive phenotype [268]. However, a recent study showed that administration of melatonin at the pre-and post-natal stages partially alleviated oxidative stress but did not improve cognitive function in a mouse model [269]. The process of programmed cell death was found to coincide with increased levels of oxidative stress, compared to control cells.…”
Section: Down Syndrome a Trisomy Of Aβpp Encoding Chromosome 21mentioning
confidence: 93%